Numerical modelling-based sensitivity analysis of fluvial morphodynamics. (January 2021) - Oliveira, Bruno; Ballio, Francesco; Maia, Rodrigo
Abstract: This study's objective is to assess the sensitivity analysis' potential for application in the context of the stochastic-input based modelling of fluvial morphodynamics. The corresponding work involved (1) an analysis of the work available in the literature and (2) an independent application of sensitivity analysis for comparison. The application of sensitivity analysis was accomplished by using a numerical hydro-morphodynamic model to represent the natural morphodynamical processes' response to the uncertainty in a selected set of variables. The resulting morphodynamical sensitivities were quantified and a characterization of the relationship between the variables' effects and morphodynamics was produced. The potential generalization of the results of sensitivity analysis for the purposes of validating stochastic modelling across different case studies was assessed. Resulting sensitivities were found to be strongly case-specific with little generalization potential, indicating that sensitivity analysis in the context of fluvial morphodynamics is likely of little scientific interest.